In Search of the Best Iron N4-Macrocyclic Catalysts Adsorbed on Graphite Electrodes and on Multi-Walled Carbon Nanotubes for the Oxidation of L-Cysteine by Adjusting the Fe(Ii)/(I) Formal Potential of the Complex - Zagal-Moya, J; Zagal-Moya, J; Silva-Rojas, J; Silva-Rojas, J; Recio-Cortes, F; Recio-Cortes, F (Springer New York LLC, 2014)
The redox potential of macrocyclic complexes is a very predictive reactivity index for the electrocatalytic activity of these molecules, and it can be easily measured under the same conditions of the catalysis experiments. It reflects directly the activity of a given complex. We have investigated the effect of the Fe(II)/(I) formal potential on the catalytic activity of a series of Fe porphyrins and Fe phthalocyanines for the electrooxidation of l-cysteine, with the complexes directly adsorbed on ordinary pyrolytic graphite or adsorbed on multi-walled carbon nanotubes (MWCNTs) deposited on graphite. A correlation of log j (at constant potential) versus the Fe(II)/(I) formal potential of the catalysts gives a volcano curve for both systems without and with MWCNTs with higher activities in the latter case. Our results clearly show that the highest catalytic activity is achieved in a rather narrow potential window of Fe(II)/(I) formal potentials of N4-macrocyclic complexes. The use of MWCNTs as supporting material for the catalysts does not change the reactivity trends of the Fe complexes. © 2014 Springer Science+Business Media New York.